Thinking outside the box means thinking outside the search engine. - Oppenheimer, Daniel M.; Patterson, Mark T. (Memory & Cognition, 2025)
This study investigates the impact of internet access on creativity and identifies potential hidden costs of internet use for groups. Using the alternative uses task, we randomized participants (N = 244) into separate conditions to generate ideas for nonstandard uses for one of two common objects—a shield or an umbrella—either with or without internet access. Nominal group analysis reveals that while individual creativity may be enhanced by internet access, groups articulate fewer novel solutions when provided internet access, suggesting that internet access may constrain collective creative fluency. We also ran a reanalysis of previous data sets on creativity and internet use and found robust converging evidence across different paradigms, coders, and contexts. We further explore robustness by examining alternative operationalizations of fluency: quality of responses, as measured by coders' evaluations of effectiveness, novelty, and subjective evaluations of creativity. While overall trends suggest an advantage for subjects who do not have internet access, this patterning depends to some degree on variation among coders. Implications for the way digital tools influence creative processes are discussed.